Encyclopedia of Industrial Biotechnology 2009
DOI: 10.1002/9780470054581.eib517
|View full text |Cite
|
Sign up to set email alerts
|

Proteins: Thermal Unfolding

Abstract: Thermal unfolding represents an important tool to evaluate protein stability and is extensively used in the development of protein‐based products. In order to assess the protein preference to maintain its folded (active) conformation, the protein is exposed to increasing levels of denaturing stress (temperature in the case of thermal unfolding) and protein stability is determined based on the stress level required to produce a significant fraction of unfolded protein. This chapter provides a description of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…For example, protein fibrils from whey protein isolate were produced by acid treatment at pH 2 for 20 h at 90 °C . For soluble proteins, heat treatment may lead to an unfolding that makes the protein backbone more accessible to attack by acids . In a previous study, we found that an insoluble protein‐rich fraction from Chlorella protothecoides was resistant to acid hydrolysis at room temperature when subjected to a treatment with 0.05–6 mol L −1 HCl .…”
Section: Introductionmentioning
confidence: 99%
“…For example, protein fibrils from whey protein isolate were produced by acid treatment at pH 2 for 20 h at 90 °C . For soluble proteins, heat treatment may lead to an unfolding that makes the protein backbone more accessible to attack by acids . In a previous study, we found that an insoluble protein‐rich fraction from Chlorella protothecoides was resistant to acid hydrolysis at room temperature when subjected to a treatment with 0.05–6 mol L −1 HCl .…”
Section: Introductionmentioning
confidence: 99%